1998
DOI: 10.1046/j.1365-2052.1998.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the bovine major histocompatibility complex DRB3 (BoLA-DRB3) alleles with occurrence of disease and milk somatic cell score in Canadian dairy cattle

Abstract: Potential associations were investigated between bovine leucocyte antigen (BoLA) alleles and occurrence of disease. Cows (Holstein n = 835; Jersey n = 66) were examined for polymorphisms of the second exon of the BoLA-DRB3 gene, using the polymerase chain reaction (PCR), followed by digestion of the amplified fragments with three restriction endonucleases. Disease occurrences were recorded for each cow throughout one lactation. Milk somatic cell count data were retrieved through the Dairy Herd Improvement reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
109
4
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 13 publications
10
109
4
6
Order By: Relevance
“…We have identified highly antigenic CD4 + T-cell epitopes on T4SS proteins VirB9-1, VirB9-2, and VirB10 presented by BoLA class II DR and DQ molecules that are encoded by alleles prevalent among Holstein cattle worldwide. Similar frequencies of the MHC class II alleles studied here were found for Holstein cattle in Japan, where the combined frequencies were 81.2%, 86.9%, 90.3%, and 95.2% in four populations studied (Miyasaka et al, 2011; Takeshima et al, 2003), in Ontario, Canada, where the combined frequency was 89.5% (Sharif et al, 1998), in Iran, where the combined frequencies were 73.2%, 75.5%, 78.1%, and 80.2% in several studies (Nassiry et al, 2008; Pashimi et al, 2009), and in Europe, where the combined frequency was 89.5% (Nassiry et al, 2008). Inclusion of VirB9-1, VirB9-2, and VirB10 peptides linked together in a multiple-antigen and peptide-based vaccine will not only provide more than one immunogenic peptide, but will offer the opportunity for increased T-cell dependent IgG responses upon infection if B cell epitopes are also included (Morse et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…We have identified highly antigenic CD4 + T-cell epitopes on T4SS proteins VirB9-1, VirB9-2, and VirB10 presented by BoLA class II DR and DQ molecules that are encoded by alleles prevalent among Holstein cattle worldwide. Similar frequencies of the MHC class II alleles studied here were found for Holstein cattle in Japan, where the combined frequencies were 81.2%, 86.9%, 90.3%, and 95.2% in four populations studied (Miyasaka et al, 2011; Takeshima et al, 2003), in Ontario, Canada, where the combined frequency was 89.5% (Sharif et al, 1998), in Iran, where the combined frequencies were 73.2%, 75.5%, 78.1%, and 80.2% in several studies (Nassiry et al, 2008; Pashimi et al, 2009), and in Europe, where the combined frequency was 89.5% (Nassiry et al, 2008). Inclusion of VirB9-1, VirB9-2, and VirB10 peptides linked together in a multiple-antigen and peptide-based vaccine will not only provide more than one immunogenic peptide, but will offer the opportunity for increased T-cell dependent IgG responses upon infection if B cell epitopes are also included (Morse et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Notably, ovine QTL for FP [23] and for MY, FY, PY and FP [21] have been previously identified around the ovine MHC-II region in Spanish Churra sheep and a Sarda×Lacaune backcross population, respectively. Moreover, in the orthologous region of BTA23, QTLs influencing milk production traits have been described [41], with at least one gene located in the MHC-II region ( BoLA-DRB3 ) showing a reported association with milk dairy traits [42].…”
Section: Discussionmentioning
confidence: 99%
“…b o la-drb3.2*16 was significantly associated with lower scs (log transformed scc ) in Holsteins (P≤0·05), and there was a significant association between b o la-drb3.2*23 and the occurrence of severe mastitis (P≤0·05) (Sharif and others 1998). No corresponding studies in sheep have been reported.…”
Section: Discussionmentioning
confidence: 99%